Reversal of fortune dividend signaling and the disappearance of sustained earnings growth - DeAngelo, Harry; DeAngelo, Linda; Skinner, Douglas J. (Journal of Financial Economics, 1996)
We study the signaling content of managers' dividend decisions for 145 NYSE firms whose annual earnings decline after nine or more consecutive years of growth. Using a variety of model specifications and definitions of favorable dividend signals, we find virtually no support for the notion that dividend decisions help identify firms with superior future earnings. Dividends tend not to be reliable signals because (i) a behavioral bias (overoptimism) leads managers to overestimate future earnings when growth prospects fade; and (ii) managers make only modest cash commitments when they increase dividends, undermining the reliability of such signals.